2006
DOI: 10.1158/1055-9965.epi-05-0293
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of the Tobacco-Specific Lung Carcinogen 4-(Methylnitrosamino)-1-(3-pyridyl)-1-Butanone by Moldovan Children

Abstract: The evidence of an association between childhood exposure to environmental tobacco smoke (ETS) and an increased risk of lung cancer is inconsistent. However, taking into account the existing association between lung cancer and adulthood ETS exposure, it is plausible that children exposed to ETS also would be at risk of developing lung cancer later in life. In this study, we investigated the uptake by Moldovan children of the tobacco-specific lung carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
(49 reference statements)
3
11
0
Order By: Relevance
“…Consistent with previous studies, we found a significant positive correlation between urinary cotinine and total NNAL (Hecht et al, 2001;Stepanov et al, 2006;Thomas et al, 2011). We also found significant positive correlations between the child urinary cotinine and total NNAL levels and indicators of tobacco smoke exposure, namely, number of hookah heads smoked and number of hours the child was exposed to hookah tobacco SHS per week.…”
Section: Continuedsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, we found a significant positive correlation between urinary cotinine and total NNAL (Hecht et al, 2001;Stepanov et al, 2006;Thomas et al, 2011). We also found significant positive correlations between the child urinary cotinine and total NNAL levels and indicators of tobacco smoke exposure, namely, number of hookah heads smoked and number of hours the child was exposed to hookah tobacco SHS per week.…”
Section: Continuedsupporting
confidence: 91%
“…Elementary school children with parental reported exposure to SHS (N = 38) in Minnesota had GM urinary levels of total cotinine and total NNAL of 12.6 ng/ml and 0.04 pmol/ml (8.4 pg/ml), respectively (Hecht et al, 2001). Children in Moldova 5-10 years old (N = 7) with reported exposure to SHS at home had GM urinary levels of total cotinine and total NNAL of 4.6 ng/ml and 0.061 pmol/ml (12.8 pg/ml) (Stepanov, Hecht, Duca, & Mardari, 2006). The majority of daily hookah smokers in our sample smoked outdoors (n = 2 indoor smokers, n = 6 outdoor smokers), a larger sample of indoor hookah smokers is warranted in future studies.…”
Section: Continuedmentioning
confidence: 99%
“…To convert nmol cotinine to ng, multiply by 176; for nicotine, multiply by 162. The mean level of total NNAL in the urine of these infants, 0.083 F 0.200 pmol/mL, was higher than in most other field studies involving NNK uptake from ETS (8,9,12,14). Figure 2 summarizes data from previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have determined levels of total NNAL in the urine of newborns, children, and adults exposed to ETS (7)(8)(9)(12)(13)(14). However, there are no data in the literature on levels of total NNAL in the urine of infants (children of age V12 months) nor could we identify studies of any other carcinogen biomarker in infants exposed to ETS.…”
Section: Introductionmentioning
confidence: 96%
“…Several previous studies have reported a statistically significant association between urinary NNAL and urinary cotinine (14,25,26) using data from 20 to 80 persons. Serum cotinine is often an indicator of exposure to SHS and, by inference, to the many toxicants associated with it.…”
Section: Cancer Epidemiol Biomarkers Prev; 19(11) November 2010mentioning
confidence: 99%